Pelanggaran Terhadap Hak Berdaulat Indonesia: Studi Kasus Tiongkok di Laut Natuna Utara - Aichel Miranda S; Ika Riswanti Putranti (Journal of International Relations Diponegoro, 2018)
In 2016-2017, Tiongkok violated Indonesia’s sovereign rights at North Natuna Sea. However there was no sanction for the problem, even though the violations committed were significant. This research aims to explain the factors that causing the violation. The Constructivism approach, especially the concept of perception, identity and culture will support the argument of this research. That Tiongkok's violating attitude is part of the country's strategic culture. Strategic culture is the main factor that causes Tiongkok 's aggressive move.  The research data is sourced from literature reviews, interviews, and analyzed using process-tracing. The results obtained from this research indicates that repeatedly violations by Tiongkok are the result of perceptions of the identity which influenced by the cultures. Thus, the violations that occur in the North Natuna Sea could be recognized as ‘mental games’. As long as Indonesia is still showing an attitude of understanding, Tiongkok's perception will not change. As long as the perception does not change, then Tiongkok will be violating Indonesia's sovereign rights over and over again.